The Siri epic as an ethnographic model for critically reimagining performance in Judges 5 and Exodus 15 - Thompson, JPW (2024)
At present, the methodological approaches used to explore performance in framed songs–specifically, Judges 5 and Exodus 15–are dominated by an inherited paradigm that largely precludes non-evolutionist models of text. This thesis argues that non-biblical ethnographic performances such as the Siri epic performance that incorporate the empirically derived insights of real or even imagined traditional performers, along with the conceptual vocabulary and epistemological categories that their reception elicits, can help us to re-imagine performance, and in so doing, unearth previously unexplored dimensions of the biblical text that evolutionist textual frameworks would otherwise foreclose.